2005
DOI: 10.1149/1.2109468
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Analysis on Transient Behavior of DMFC Anodes during Preconditioning Process

Abstract: Transient behavior of direct methanol fuel cells ͑DMFCs͒ during the preconditioning process has been investigated with a focus on changes manifested in the anode by using an electrochemical impedance spectroscopic analysis. Preconditioning of membrane electrode assembly ͑MEA͒ is essential to achieve maximum cell performance, and the time required to accomplish the conditioning may vary depending on the methods that are adopted. Preconditioning temperature substantially influences the behaviors of MEAs, and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The Nafion-MEA displays a low cell voltage (i.e., 0.33 V) due to a high activation polarization. Preconditioning the Nafion-MEA overnight at 340 K in recirculating 1.8 ml.min -1 2 M methanol solution and 10 sccm dry O 2 resulted in a higher cell voltage of 0.54 V. The improved cell performance after preconditioning was attributed to catalyst activation [62][63][64] and changes in the cell's electronic properties [64][65][66]. It is evident from Fig.…”
Section: Zeolite Micromembranesmentioning
confidence: 91%
“…The Nafion-MEA displays a low cell voltage (i.e., 0.33 V) due to a high activation polarization. Preconditioning the Nafion-MEA overnight at 340 K in recirculating 1.8 ml.min -1 2 M methanol solution and 10 sccm dry O 2 resulted in a higher cell voltage of 0.54 V. The improved cell performance after preconditioning was attributed to catalyst activation [62][63][64] and changes in the cell's electronic properties [64][65][66]. It is evident from Fig.…”
Section: Zeolite Micromembranesmentioning
confidence: 91%
“…Previous studies [2,3] indicate that the temperature plays a crucial role on the in situ activation procedure, namely affecting the development of the triple phase boundary. From the impedance experiments it was shown that using different proton exchange membranes results in different double layer capacitances after the activation procedure.…”
Section: The Effect Of the Temperature On The In Situ Activation Procmentioning
confidence: 99%
“…Beyond these challenges, the development of quick and effective procedures to ensure maximum performance of the membrane electrode assembly (MEA) during the start-up or after resting periods is also very important. These procedures have received scarce attention from the scientific community and there is a clear lack of available information in the open literature [2,3]. It is known that a MEA performs below the nominal power whenever started from fresh or after a resting period [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies showed that EIS results could provide information of individual fuel cell component [12][13][14][15][16]. Müller and Urban [8] suggested a method to separate anode and cathode impedance by measuring anode and full cell impedance data, respectively.…”
Section: Introductionmentioning
confidence: 99%